Perancangan User Experience pada Situs Web Rumah Sakit Umum Asri Purwakarta dengan menggunakan Metode Human Centered Design (HCD) dan User Experience Questionnaire (UEQ) - Irfan Aufa Ramadya; Satrio Hadi Wijoyo; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
PT Asri Medical Center has a health service facility in the form of a general hospital, the hospital wants a facility in the form of a website to promote the hospital and make it easier for the community in terms of health services. Therefore it is necessary to design a website that is good, easy to use and can meet user needs. This research was conducted with the aim of producing a desktop version of the user interface design of the Asri Purwakarta General Hospital website using the Human Centered Design (HCD) method which consists of 4 phases. The first phase of defining user context aims to identify users of the website through user identification by online observation and interviews, identifying user characteristics and determining user goals and tasks. The second phase performs a user needs analysis including a list of user requirements and a list of features on the website. The third phase of designing a solution begins with the creation of a web site design framework that has been validated, then proceeds to produce a high-fidelity prototype (High-Fidelity). The last phase is evaluating the solution design by giving User Experience Questionnaire (UEQ) questions to users and the hospital's response to the desktop version of the website prototype that has been created. The results of the test using the UEQ assessment, which has a positive category mean value with all UEQ scales in the very good category. As well as responses from users including hospital stakeholders and the general public as a whole are good.